Pengaruh Persediaan Bahan Baku dan Kualitas Bahan Baku terhadap Hasil Produksi pada PT. Kreasi Kemas Indonesia - Utari Dyah Ayu Astami; Daman Sudarman (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to analyze the effect of raw material inventory and raw material quality on production results at PT Kreasi Kemas Indonesia. This research uses quantitative methods with saturated sampling techniques involving 50 employees as respondents. The results showed that raw material inventory had a positive and significant effect on production output (tcount 5.206 > ttable 2.011), as well as the quality of raw materials which had a significant effect (tcount 4.424 > ttable 2.011). These findings confirm the importance of inventory management and raw material quality control in maintaining productivity.